INTEGRASI PEMIKIRAN IMAM AL-GHAZALI & IVAN PAVLOV DALAM MEMBENTUK PRILAKU PESERTA DIDIK - Umaruddin Nasution; casmini casmini (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2020)
ABSTRAK This study aims to analyze the relationship between the thoughs of al-Ghazali and Ivan Pavlov in establishing educational behaviours. In this study took two figures: The first Imam Al-Ghazali, which is one of the Sufi figures using the riyadhoh concept and dubbed it the hujjatul Islam and secondly Ivan Patrovich Pavlov which is one of the behavioristik learning theory using the clasical conditioning concept dubbed the father behavioristic theory. This type of research is are search library based on the books of the two figures. The approach philosophical-historical and content analysis are a reference in providing an explanation of the results of the data found. The results of this study indicate that by taking the road to habituation will be able to provide a change in one is behavior. Refraction is done in three stages, namely takhalli (unconditioning stimulus), tahalli (conditioning stimulus), and tajalli (conditioning response) in order to reflect the good behavior become a habitual hai'ah in self learners.